Adição de carvão vegetal em cultivo de arroz irrigado: efeitos sobre os indicadores físicos e químicos do solo, desempenho do arroz; emissões de metano e viabilidade econômica do cultivo contínuo, em Arari-MA - Sousa, Aurea Maria Barbosa de (2011)
The rice cultivation practiced for years in Maranhao Lowlands has proven unsustainable to smallholders, who face social, economic and ecological problems. This study proposes to test the economic advantages of continuous rice cultivation, to increase yields over time, with two annual crops, one in the rainy season and the other in the dry season. This system can promote intensive cultivation of the soil exhaustion and even enhance methane emissions. Therefore, the application of charcoal associated with different doses of fertilizers can improve the productive aspects of culture, the soil fertility and reduces methane emissions. Thus, samples were collected and analyzed dry and flooded soil, samples of rice plants, and quantified their performance, and carried out sampling and analysis of methane emissions. The addition of charcoal or fertilizer rates did not produce significant increases in yields, but charcoal has reduced levels of ammonia in 44% and increased the K in the soil, and promote the reduction of methane emissions of up to 7.3 times the rice. The continuous cultivation of rice was found to be profitable, but not outsourced labor. However, in the case of smallholders, labor is usually of the family. Thus, it is possible to get an increase of 3.6 Mg ha-1 in the annual crop or R$ 1,244.50 in the rainy season.